Действие интенсивности замеса теста на его водопоглотительную способность - Юрчак, Вера Гавриловна; Скорикова, Анна Ивановна; Ройтер, Исаак Менашевич (My University, 1975)
Изучено влияние замеса теста в машине периодического действия в течение 6 и 20 мин. и в ротационной машине на физические свойства теста разной влажности. Определяли консистенцию теста на валориграфе и предельное напряжение сдвига с помощью пенетрометра. Установлено, что усиление механического воздействия на тесто во время замеса позволило повысить его влажность на 1 – 1,5 % при сохранении таких же физических свойств, как и при обычном 6-минутном замесе. There was investigated the influence of dough kneading in the machine of 6 and 20 min periodic action and in the rotary machine on physical properties of the dough of various moisture content. There also was determined the dough consistency by using valorigraph and limiting shear stress was determined by using penetration-type gauge. It was established that the enhancement of the mechanical effect on the dough during kneading allowed to increase its moisture content by 1 - 1.5% while maintaining the physical properties same as during the conventional 6-minute kneading.
Keywords: дежевая машина; ротационная машина; длительность замеса; частота вращения; свойства теста; tub machine; rotary machine; duration of kneading; rotating speed; dough properties; кафедра технології хлібопекарських і кондитерських виробів